2001
DOI: 10.4315/0362-028x-64.3.355
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a 5′-Nuclease (TaqMan) Assay for the Detection of Virulent Strains of Yersinia enterocolitica in Raw Meat and Tofu Samples

Abstract: Culture methods for detecting virulent Yersinia enterocolitica require selective enrichment and a series of confirmatory tests that are time-consuming, costly, and laborious. The objective of this study was to evaluate a fluorogenic 5'-nuclease assay for detecting the enterotoxin yst gene of virulent Y. enterocolitica in pure cultures, inoculated ground pork samples, and naturally contaminated food samples. These results were then compared with "gold standard" methods recommended by the U.S. Food and Drug Admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
1

Year Published

2002
2002
2007
2007

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 27 publications
2
17
1
Order By: Relevance
“…However, the detection limit of the PCR reaction was 1-10 cfu per PCR. This is in consistent with earlier studies (Boyapalle et al, 2001;Vishnubhatla et al, 2001).…”
Section: Resultssupporting
confidence: 83%
“…However, the detection limit of the PCR reaction was 1-10 cfu per PCR. This is in consistent with earlier studies (Boyapalle et al, 2001;Vishnubhatla et al, 2001).…”
Section: Resultssupporting
confidence: 83%
“…In the same study, the isolation rates of Y. enterocolitica in ground beef and pork were also elevated. The contamination level of these products was obviously very high, because the culture method used was able to identify Y. enterocolitica only when 10 6 CFU or more organisms per g were present (152). The occurrence of pathogenic Y. enterocolitica was also shown to be clearly higher by the PCR assay than by culturing (Table 5).…”
Section: Food Samplesmentioning
confidence: 85%
“…For artificially contaminated pork, Boyapalle et al (20) have shown that the TaqMan assay targeting the ail gene was 100 to 1,000 times more sensitive than the traditional PCR assay with gel-based detection and 10,000 times more sensitive than the culture method. Visnubhatla et al (152) used the same TaqMan assay, but instead of ail, they targeted the yst gene. This was the first time when a high occurrence of yst-positive Y. enterocolitica was detected in retail ground beef.…”
Section: Food Samplesmentioning
confidence: 99%
“…One can simultaneously analyze eight pathogenic or specific genes of food-or waterborne pathogens in five stool specimens by using duplex LC-PCR and 32 capillary tubes. Single or multiple real-time PCR assays were reported for detection of one species among foodor waterborne pathogens, such as EHEC O157 (1,11,14,29), Salmonella (5,10,17), Y. enterocolitica (30,35,36), Campylobacter jejuni (19,25,39), V. cholerae (21), V. parahaemolyticus (13), P. shigelloides (20), and S. aureus (28,32). Nineteen pairs of primers for food-or waterborne pathogens were selected from earlier publications (Table 2), and one pair of primers for Y. enterocolitica and Y. pseudotuberculosis was constructed.…”
Section: Discussionmentioning
confidence: 99%